TANTANGAN METODELOGIS KUANTIFIKASI SOSIOLOGI - Ali Anwar Yusuf (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2017)
Uncertainty in the nature of human behavior and interaction patterns as part of thecommunity, in sociology, has been avoided by the use of quantitative methods such as chaostheory, non linearism, and dynamics of complex systems. As for the facts and mutualdependence globalizing processes and social structures, can be overcome by applyingBayesian statistical methods and Boolean logic. Similarly, with limited explanation ofstatistical methods, can be offset by assessments or base react to these conditions, as explainedby the theory of Black Swan. Overall these facts are methodological challenges faced bysupporters of quantitative sociological research. Theories in sociology more produced byqualitative research, but with awareness of the limitations of these and deal with adaptation ofcurricula and updating methods and techniques of statistical analysis and deepening the skillsin modeling statistical and mathematical, so expect sociological theories results ofquantitative research, will be produced and developed in sociology lesson in all strata oflearning.Keywords: chaos theory, non linearism, the dynamics of complex systems, the theory ofBlack Swan, Bayesian statistics, Boolean logic, quantitative research, qualitative research.